Sosialisasi Pencegahan Stunting di Desa Teratak Lombok Tengah - Krosby , Sebtiara Syahrani; Nanda Safitri; Khatimah, Husnul; Satifa, Anggun Aprilia; Dirja, Jaka Prawira; Hidayat, Rahmad; Rahmi, Siti Atika (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
Stunting is a condition of failure to grow and develop in children due to lack of nutritional intake. There are several main causes of stunting in children, one of which is the lack of public knowledge about stunting itself. The purpose of this socialization is to increase the knowledge of participants (community) about stunting, its causes and prevention, as well as the introduction of additional food (PTM) such as processed avocado pudding aimed at the community: pregnant women, adolescents, and stunting toddlers. The method of implementing this stunting prevention socialization uses a direct observation method (field visit) which consists of planning activities, activity preparation meetings, and hearings. The results of the implementation of stunting socialization in Teratak Village show that the participants are very enthusiastic in learning new things and adding knowledge and insight, and also always follow the socialization programs carried out by Muhammadiyah Mataram University students, especially if there are demonstration activities that will attract participants so that they understand more easily. And it is hoped that the community who will conduct the next socialization will provide more thorough directions and direct demonstrations.